Sustaining the U.S. Air Force nuclear mission - Snyder, Don, 1962- (Technical report (Rand Corporation) ;, 2013)
The United States' nuclear deterrence is no more effective than its ability to carry out nuclear operations and other states' perceptions of this ability. The U.S. Air Force (USAF) has prioritized the reinvigoration and strengthening of its nuclear enterprise. However, there are inherent challenges to sustaining the capabilities of nuclear systems of systems. Perhaps the most pressing challenge currently facing the Air Force nuclear enterprise is sustaining the mission in the face of budgetary constraints. This report proposes possibilities for addressing this challenge. Coordination is key to this approach. Individual platforms must work together seamlessly for the nuclear system of systems to perform successfully. Any slippage in one system may cause schedule delays and increased costs for all other systems working in concert. This report outlines a double-layered framework for managing nuclear sustainment. This framework consists first of a set of sustainment plans for each system that follow a common format. The second layer, an overarching Air Force Nuclear Architecture and Mission Sustainment Plan, pulls together salient information from the individual, system-level plans to compile a master schedule for long-term mission sustainment. This framework should strengthen future nuclear deterrence capabilities through better planning and programming for the sustainment of these missions in the present.